Shared Service Center as a strategic enabler in M&A : Supporting M&A integration through HR service platform - Haavisto, Tommi (fi=Turun yliopisto|en=University of Turku|, 2018)
Over the recent years, several multinational enterprises have established Shared Service Centers (SSC) in attempt to create organizational flexibility. Organizational flexibility refers to the organization’s ability to adapt in the event of change, such as mergers and acquisitions (M&A). The goal of this thesis is to assess how SSC could support M&A integration process. The study was done from the perspective of Human Resources (HR) function, as it has a significant impact on the process. Many sources suggest that SSC would have a positive impact on realizing acquisition synergies. However, the evidence have remained very thin. This study aims to understand how SSC could be utilized in M&A operations. The literature review presents the key factors of the topics of SSC and M&A integration. It builds a baseline for the case study of Cargotec Corporation. The case company is a serial acquirer which has established a SSC in 2017. The research was conducted as a qualitative case study in which the empirical data was collected through theme interviews, observation and text analysis. The interviewees were selected based on their experience on SSC and M&A operations and their role in the case company. The empirical data revealed that the case company had significant challenges in human integration as there has been several loose integrations, which have created complexity. The case company aims to tackle these challenges through unified SSC platform. Based on the empirical findings and literature review, it was concluded that M&A integration consists of three dimensions, which are strategic, operational and learning. Strategic activities focus on planning the value creation while operational dimension refers to activities that enable the value creation. Finally, learning refers to gathering acquisition experience through reviewing the process following the integration project. The focus points in M&A integration are defining value creation targets and integration approach, focusing on human integration, making structural changes and ensuring business continuity. It was concluded that SSC has the biggest impact in the enabling operational activities. SSC is able to support implementation phase of the integration by offering transactional HR services. This would enable business leaders to concentrate more on human integration and value creation as the transactional work is lead from SSC. Consequently, SSC can be seen as a strategic enabler in M&A.